Case Report: Early bilateral capsular contraction syndrome associated with Epstein–Barr virus-positive uveitis after cataract surgery - Ying Li; Zhouyang Ye; Minhong Fei (Frontiers in Medicine, 2026)
Objective To report a case of capsular contraction syndrome complicated by viral uveitis during the early postoperative period after bilateral cataract surgery. Methods A retrospective case report was conducted. Results A 74-year-old woman with no significant medical history developed bilateral capsular contraction syndrome one month after bilateral cataract surgery. Further ophthalmic evaluation revealed bilateral uveitis. Laboratory testing and metagenomic next-generation sequencing identified Epstein–Barr virus (EBV) in both peripheral blood and aqueous humor samples. Conclusion EBV-associated uveitis may have contributed to the early development of bilateral capsular contraction syndrome in this patient after cataract surgery. In patients presenting with postoperative uveitis accompanied by capsular contraction, underlying viral infection should be considered as a potential contributing factor.